Similarity Reductions of $(2+1)$-dimensional Equal Width Wave Equation - G. Bharathi; R. Asokan (International Journal of Mathematics And its Applications, 2016)
It has been shown to have solitary wave solutions and to govern a large number of important physical phenomena such as shallow water waves and plasma waves.